Assessment of Agricultural Information Needs in African, Caribbean and Pacific (ACP) States: Eastern Africa: Country study Tanzania - Shetto, Mary C. (Technical Centre for Agricultural and Rural Cooperation, 2008)
The study aimed to provide insight on status of infrastructure, information services and ICM capacity of institutions involved in agriculture and rural development, information and capacity building needs in the area of ICM identified for key institutions and potential CTA partners involved in ARD and potential strategic partners for CTA activities and services identified and baseline data on the status of ICM and ICT in ARD compiled for monitoring purposes and improved outreach...